The effect of query complexity on Web searching results - B.J. Jansen (Information Research: An International Electronic Journal)
This paper presents findings from a study of the effects of query structure on retrieval by Web search services. Fifteen queries were selected from the transaction log of a major Web search service in simple query form with no advanced operators (e.g., Boolean operators, phrase operators, etc.) and submitted to 5 major search engines - Alta Vista, Excite, FAST Search, Infoseek, and Northern Light. The results from these queries became the baseline data. The original 15 queries were then modified using the various search operators supported by each of the 5 search engines for a total of 210 queries. Each of these 210 queries was also submitted to the applicable search service. The results obtained were then compared to the baseline results. A total of 2,768 search results were returned by the set of all queries. In general, increasing the complexity of the queries had little effect on the results with a greater than 70% overlap in results, on average. Implications for the design of Web search services and directions for future research are discussed.